Linear Precoder Design for SWIPT in MIMO Broadcasting Systems With Discrete Input Signals: Manifold Optimization Approach - An-An Lu; Xiqi Gao; Zheng, Yahong Rosa; Chengshan Xiao (IEEE transactions on communications, 2017)
In this paper, we investigate the design of linear precoders for simultaneously wireless information and power transfer (SWIPT) in a multi-input multi-output (MIMO) broadcasting system with discrete input signals. The considered system model consists of one base station (BS), one information receiver (IR), and one energy receiver (ER). The design objective is to maximize the input-output mutual information of the IR subject to the power constraint and the harvested energy requirement for the ER. We derive the structure of the optimal linear precoder by using manifold optimization, and propose an algorithm to find the optimal precoder. Simulation results show that the proposed algorithm can achieve better performance than the time sharing scheme and the Gaussian optimal precoder when Gaussian inputs are replaced by discrete input signals.